Multi‐functional high‐isolation dual antenna for controllable wireless charging and NFC communication. Issue 13 (1st June 2014) - Lee, W.‐S.; Kim, D.‐Z.; Yu, J.‐W.
Abstract : For stable wireless charging and reliable data communications in mobile devices, the proposed high‐isolation dual antenna operates at two different frequency bands such as 6.78 MHz at wireless charging and 13.56 MHz at near‐field communication (NFC). To increase the isolation between antennas, the proposed dual antenna has an antiparallel coil structure. It has achieved approximately more than 20 dB isolation between antenna ports.